The crystal structure of the co-crystal composed of benzhydrazide and 5-aminoisophthalic acid, C8H7NO4⋅C7H8N2O - Bourletidis How Jeraldine Maire; Scheepers Matthew C.; Lemmerer Andreas; Smith Mark G. (Zeitschrift für Kristallographie - New Crystal Structures)
C8H7NO4⋅C7H8N2O, monoclinic, P21/n (no. 14), a = 18.3690(6) Å, b = 3.8010(1) Å, c = 21.5232(7) Å, β = 108.867(1)∘, V = 1422.02(8) Å3, Z = 4, R gt(F) = 0.0340, wR ref(F 2) = 0.0959, T = 173 K.